Work-Life-Blending: Chancen, Herausforderungen und Strategien für eine harmonische Verzahnung von Beruf und Privatleben - Marcel Dulgeridis; Elisabeth Dewaldt (IU Internationale Hochschule, 2024)
– This paper examines the evolution from traditional Work-Life Balance to the modern concept of Work-Life Blending. While Work-Life Balance aims for a clear separation between professional and personal life, Work-Life Blending integrates these spheres, reflecting the realities of a digitalized world where boundaries are increasingly fluid. The paper assesses the theoretical foundations of Work-Life Blending, including Boundary Theory, Role Theory, Technostress Model, and Work-Family Enrichment Theory. It critically evaluates the benefits of Work-Life Blending, such as increased flexibility, autonomy, and improved work satisfaction for employees, alongside challenges like the risk of burnout, technostress, and the need for new leadership strategies. Case studies from companies like Google, SAP, and Dell demonstrate the implementation of Work-Life Blending practices. The paper also provides recommendations for employers, employees, and policymakers to optimize the adoption of Work-Life Blending. It emphasizes the importance of technological innovation, cultural adaptation, and supportive infrastructure. Finally, the paper projects that Work-Life Blending will remain a critical element of the modern workplace, requiring ongoing research, interdisciplinary collaboration, and flexible adaptation strategies to maximize its benefits and address its challenges.
Keywords: 650; Boundary Theory; Case Studies; Corporate and Leadership Strategies; Digital Transformation; Employee Well-Being; Flexible Work Models; Future Workplace Trends; Job Satisfaction; Role Theory; Technostress; Work-Life Balance; Work-Life Blending